2022
DOI: 10.1186/s12884-022-04507-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blister packaging Iron and Folate on adherence to medication and hemoglobin levels among pregnant women at National Referral Hospital antenatal clinics in a low to middle income country: a Randomised Controlled Trial (The IFAd Trial)

Abstract: Introduction Anemia in pregnancy is an important global public health problem. It is estimated that 38% of pregnant women worldwide are anemic. In Africa, literature from observational studies show 20% of maternal deaths are attributed to anemia. In Uganda, 50% of pregnant women have iron deficiency anaemia. The proportion of pregnant women receiving Iron-Folic acid (IFA) supplementation has improved. However, the number of IFA pills consumed is still low. We carried out a randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 23 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…The majority of the prenatal women in the current study were between the ages of 25 and 30 years. However, Khorshid et al [ 13 ], Byamugisha et al [ 14 ], Ahamed et al [ 15 ], Kaundal et al [ 16 ], Sunuwar et al [ 12 ], Abujilban et al [ 17 ], Srivastava et al [ 18 ], Nahrisah et al [ 19 ], Bumrungpert et al [ 20 ], Sontakke et al [ 21 ], Mithra et al [ 22 ], Dutta et al [ 23 ], Kassa et al [ 24 ], and Boti et al [ 25 ] reported mean ages ranging from 22-30 years of age. Similar to a study done by Sontakke et al [ 21 ], pregnant women in the present study were equally divided according to their parity status as nulliparous and multiparous in intervention and non-interventional groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the prenatal women in the current study were between the ages of 25 and 30 years. However, Khorshid et al [ 13 ], Byamugisha et al [ 14 ], Ahamed et al [ 15 ], Kaundal et al [ 16 ], Sunuwar et al [ 12 ], Abujilban et al [ 17 ], Srivastava et al [ 18 ], Nahrisah et al [ 19 ], Bumrungpert et al [ 20 ], Sontakke et al [ 21 ], Mithra et al [ 22 ], Dutta et al [ 23 ], Kassa et al [ 24 ], and Boti et al [ 25 ] reported mean ages ranging from 22-30 years of age. Similar to a study done by Sontakke et al [ 21 ], pregnant women in the present study were equally divided according to their parity status as nulliparous and multiparous in intervention and non-interventional groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a study done by Sontakke et al [ 21 ], pregnant women in the present study were equally divided according to their parity status as nulliparous and multiparous in intervention and non-interventional groups. There were fewer multiparous women than nulliparous in previous studies undertaken by Wiradnyani et al [ 26 ], Byamugisha et al [ 14 ], Nahrisah et al [ 19 ], and Kassa et al [ 24 ]. Comparatively, only a few other studies by Boti et al [ 25 ] and Khorshid et al [ 13 ] included more nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Iran's research analyzed the impact of Short Message Service messaging on compliance (Khorshid et al, 2014). Indonesia's deployment of mobile management software to monitor the compliance of Fe supplementation (Rukmaini, 2018), a low-to middle-income country's usage of packing in blisters for Iron and Folate in an IFAd trial (Byamugisha et al, 2022), and the use of integrated pictorial handbook counseling (Nahrisah et al, 2020). However, some interventions did not improve anemia after the end of the experiment (Byamugisha et al, 2022;Rukmaini, 2018).…”
Section: Introductionmentioning
confidence: 99%